Scenario of changing dynamics in production and productivity of major cereals in India - HANDRAL, ANKHILA R; SINGH, ALKA; SINGH, D R; SURESH, A; JHA, G K (The Indian Journal of Agricultural Sciences, 2017)
Cereals occupy prime position in diet composition of all human beings, with rice, wheat and maize being the major staple cereals with more than 70% share among all the food grains. With the inception of green revolution, India from being a food deficit and net importer of food grains not only became self reliant but also one of the major exporters of food grains with the adoption of modern wheat and rice varieties. Thus the present study was undertaken to analyze the trends in area, production and productivity of rice, wheat and maize for the period 1990-91 to 2012-13 obtaining data from the Directorate of Economics and Statistics, Ministry of Agriculture, Government of India, New Delhi. The compound annual growth rate (CAGR) and coefficient of variation were also used to see the growth patterns and instability in the production and productivity of these cereals overtime. The results showed that in both rice and wheat instability increased in area, production and productivity but most of the states registered an increasing growth trends during the period. Notably Maize showed increase in area, yield and production since 2000 due to its increasing demand for industrial usage and had significant growth in the decade due to its growing commercial value with emergence of promising new hybrids. The study points out to the significant intervention of policy to helpmaintain stability in case of major cereals of India’s food security.